Predictors of breast radiotherapy plan modifications: Quality assurance rounds in a large cancer centre. Issue 1 (January 2015) - Lymberiou, Timothy; Galuszka, Susanne; Lee, Grace; Xu, Wei; Fyles, Anthony; Su, Susie; Purdie, Thomas G.; Catton, Pamela; Chung, Caroline; Dinniwell, Robert; Koch, Anne; Levin, Wilfred; et al.
Abstract: Background and purpose: This study describes the process and outcomes of breast radiotherapy (RT) quality assurance (QA) rounds, seeking to identify variables associated with plan modifications. Materials and methods: Real-time data were prospectively collected over 2 years. Descriptive statistics determined the proportion of cases requiring no (A), minor (B), or major (C) modifications, which were then subjected to univariate and multivariate analyses. Results: A total of 2223 breast cancer QA cases were reviewed; 47 cases (2.1%) underwent a minor, and 52 cases (2.3%) required a major modification. Common changes included boost, volume, seroma, and bolus. On univariate analysis, regional nodal irradiation (RNI), tumour size, and axillary node dissection were significantly associated with major modifications. Upon multivariate analysis, the only independent predictor was RNI (OR 2.12, p = 0.0075). For patients with no RNI, <2 cm tumours, no axillary lymph node dissection, and no boosts ( n = 420); the likelihood of category C was only 1.4%. Conclusions: It is feasible to conduct QA review for all breast cancer cases prior to commencing RT. Patients undergoing RNI had a higher likelihood of plan modifications; a group with low risk of modification was identified, which could direct future re-structuring of QA rounds.